The use of digital platforms by citizen aid actors during the Ukraine humanitarian crisis - Sithole, Tererai Obey (Frontiers in Human Dynamics, 2024)
At the beginning of the Ukraine refugee crisis, ordinary citizens stepped up to spontaneously coordinate various humanitarian responses to support affected populations. In this paper such individuals who spearheaded or coordinated this form of spontaneous humanitarian aid are referred to as citizen aid actors (CAA). This paper explores the work of citizen aid actors in Poland, a country which received many of the people displaced by the war in Ukraine. It takes a qualitative approach where interviews, participant observation, and analysis of relevant online material about the studied citizen aid actors were used as methods of collecting data. The findings show how these actors used different digital platforms to establish, organize and sustain their interventions. The paper is connected to the concept of affordances and argues that citizen aid actors relied on the features available on digital platforms to attain their goals. On the one hand, it highlights some elements to demonstrate how specific digital platforms contributed to the overall accomplishment of the work done by CAAs. On the other hand, it also highlights how it can be problematic when the actors largely rely on digital platforms to get their work done. This is addressed by outlining some potential risks, including concerns about trolls, fake news, and internet disruptions.